Diastereoselective synthesis of isochromans via the Cu(ii)-catalysed intramolecular Michael-type trapping of oxonium ylides. Issue 89 (24th October 2018) - Alavala, Gopi Krishna Reddy; Sajjad, Farrukh; Shi, Taoda; Kang, Zhenghui; Ma, Mingliang; Xing, Dong; Hu, Wenhao
Abstract : A highly diastereoselective approach for the rapid construction of an isochroman skeleton was achieved by the copper(ii )-catalyzed transformation of alcohol-tethered enones and diazo compounds. Abstract : A highly diastereoselective approach for the rapid construction of an isochroman skeleton was achieved by the copper(ii )-catalyzed transformation of alcohol-tethered enones and diazo compounds. This transformation was proposed to proceed through the intramolecular Michael-type trapping of an in situ generated oxonium ylide intermediate. The copper(ii ) catalyst may play a dual role in catalyzing diazo decomposition as well as activating the enone unit. With this method, a series of 3, 4-substituted isochromans were obtained with excellent diastereoselectivities under very mild reaction conditions.